Refugees, migrants, visitors and internally displaced persons: investigating acculturation in Academia. Issue 1 (2nd January 2016) - Rowe, Nicholas; Martin, Rose; Knox, Sarah; Mabingo, Alfdaniels
ABSTRACT: What is the boundary of the academic space, and who can belong within it? The migration of skilled practitioners into Academia from other workplaces brings with it the opportunity to expand the understandings and functions of higher education. Similar to processes of geographic/political migration, the acculturation resulting from this professional resettlement can lead to the assimilation, integration, separation or marginalization of academic migrants. Within this article, we explore how differing pathways within and into Academia from other professional contexts can impact upon an academic immigrant's sense of belonging. Adopting the roles of an economic migrant, a refugee, an internally displaced person and a temporary visitor, we entangle our professional narratives with themes of citizenship and migration, to examine the complexity of integration and inclusion within higher education. Our imaginative reconceptualization of academic migration leads into a discourse analysis guided by contemporary theory on acculturation and recollections of the acculturative queries we have encountered on our own journeys.